(untitled) (Research, Society and Development, 2020)
The study aimed to map the spatial distribution and characterize individuals diagnosed with leprosy in the city of Picos, a hyper-endemic municipality for the disease, located in the semi-arid region of the state of Piauí, northeast region of Brazil. This is an ecological, analytical and exploratory study carried out through access to compulsory notification forms contained in the Epidemiological Surveillance, where descriptive statistics such as absolute and relative frequencies, proportion ratio and calculation of incidence were performed. After verifying autocorrelation using the global Moran index, local autocorrelation was evaluated using the LISA (Local Indicators of Spatial Association) using Moran Maps (Moran Maps) for the spatial representation of the Moran scattering diagram. The results showed that the average detection rate in the period was 45.60 / 100 thousand inhabitants in the general population and 6.4 / 100 thousand inhabitants in children under 14 years old. A higher percentage of reported cases was observed in adult individuals, male, incomplete elementary school, brown color and urban residence area. There were similar percentages in leprosy notifications in primary care and in secondary care points (50.5% and 49.5%) respectively. It showed that the disease’s endemicity is widespread in all regions of the city and most neighborhoods were hyperemic. The formation of a high / high cluster in specific regions of the city. The data presented are elements to be considered in the organization and strengthening of health services.